Texting while piloting: A simulation study comparing verbal and written navigational instructions in shore-based deep sea pilotage - Eklund, Peter; Göransson, Henrik (My University, 2013)
Piloting has been used in seafaring throughout all times. The technological advances in recent years have led to much discussion of whether shore-based pilotage should be used, but not as much discussion about how such shore-based pilotage should be conducted. The purpose of this thesis is to investigate a specific part of the subject of shore-based pilotage; the difference between how piloting instructions transmitted using two different modes of communication, written and verbal, influence the behaviour of bridge officers when navigating, during shore-based deep sea pilotage. In order to investigate this, an observational study was conducted in the Bridge Operations Simulator at Chalmers Campus Lindholmen’s Simulation Centre. In the study, the participants navigated through a part of route-T through the Great Belt strait, while receiving navigational instructions over either VHF radio or a text based chat. After the simulation, a debriefing was conducted, in order to find out how the participants experienced the simulation, and to receive their comments regarding the use of the two modes of communication. The study pointed to a number of tendencies, that combined led to the conclusion that the option of transmitting appropriate parts of the navigational instructions over a text based medium, when designing a system for shore-based deep sea pilotage, should not be overlooked.
Keywords: Transport; Transportteknik och logistik; Annan teknik; Transport; Transport Systems and Logistics; Other Engineering and Technologies